Dynamism in the urban society of Damascus : the Ṣāliḥiyya Quarter from the twelfth to the twentieth centuries - Miura, Tōru, 1953- (Islamic Area Studies, 2015)
This book presents a new perspective on Islamic urban society: a dynamism of social networking and justice which caused both rapid development and sudden decay in the Ṣāliḥiyya quarter. Founded in the northern suburbs of Damascus by Hanbali ulama who migrated from Palestine to Syria in the mid-12th century, the quarter developed into a city through waqf endowments. It has attracted the attention of historians and travelers for its unique location, popular movements and religious features. Through the study of local chronicles, topographies and archival sources and through modern field research, Toru Miura explores the history of the Ṣāliḥiyya quarter from its foundation to the early 20th century, comparing it to European, Chinese and Japanese cities.